Archaeological Exploration of the Kusumi River Valley: Insights from Unearthed Sites in Nayagarh District - Venkatesh, Narayana (Journal of Social Science and Humanities, 2026)
The present study on unearthed archaeological sites around Kusumi River, which is considered to be one of the major tributaries of river Mahanadi, filled with archaeological settlement remains and monuments. The Kusumi River has been played a significant role in the history of Nayagarh District, Odisha. The bank of Kusumi River was overflowed due to flood in that river which created fertility of the soil. The fertility of the soil helped in ample production of crops which sustained in the life of the people of that land and contributed to the growth of socio - politici - econonic and cultural life of people Nayagarh district. This river originated from Bhanjanagar (Panchabuti) and it falls at bhategarh near Kantilo the famous for Nilamadhava Vishnu temple in the river Mahanadi. The Kusumi river is dotted with for archaeological remains. we also found some number of on unearthed archaeological sites, which basically appeared on the banks of river Kusumi, such as Asuradhipa on the right bank of Kusumi river near Sarankula, Ralabagarh on the left bank of Kusumi river near the village of Ambapada and last one is paikabankatara, on the left bank of Kusumi river near Dhalamaska. Although, these sites are not excavated still now but I have found some archaeological artefacts. From a small exploration, such as two hand axes and different types and different shapes potsherds like bowl, rim part of potteries ant etc.